LITERASI RELASIONAL BERBASIS 1 KORINTUS 13:4-8 UNTUK PENCEGAHAN TOXIC RELATIONSHIP: PENDIDIKAN KASIH AGAPE SEBAGAI STANDAR HEALTHY RELATIONSHIP PADA PEMUDA KRISTEN - Elfin Rara (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
The inability of Christian youth to distinguish between healthy relationships and toxic relationships is a major cause of the high rates of intimate partner violence in dating relationships. This research aims to develop a relational literacy education model based on 1 Corinthians 13:4-8 to prevent toxic relationships and promote healthy relationships among Christian youth. The study employs a qualitative methodology using literature review design, collecting and analyzing over 30 academic sources through thematic content analysis. Research findings demonstrate that agape love in 1 Corinthians 13:4-8 provides a clear theological standard for evaluating relational health, characterized by patience, generosity, non-jealousy, and selflessness. The developed relational literacy education model integrates three learning dimensions: (1) theological consciousness and critical evaluation, (2) communication skills and boundary-setting, and (3) emotional-spiritual awareness. This model can be implemented through youth discipleship programs, pre-marital counseling, and support groups within churches. This research contributes theoretically and practically to the development of pastoral counseling and Christian religious education in preventing relational violence among youth.